Quantitative Analysis of Etimicin by 1H NMR Spectroscopy - Liu, Shuyu; Yao, Shangchen; Hu, Changqin (Asian Journal of Chemistry, 2013)
A simple and rapid quantitative NMR assay was developed to measure the etimicin. The response linearity was ensured by linear determination factors R2, which was 0.9989. The quantitation of the etimicin was reproducible and the method relative standard deviation is 0.573 %. The relative errors, measured against the labeled amount of etimicin, ranged from 0.47-0.68 %.